An investigation into the possible physiological mechanisms associated with changes in performance related to acute responses to different preactivity stretch modalities - Fletcher, I. M.; Monte-Colombo, M. M. (Applied Physiology, Nutrition, and Metabolism, 2010)
The aim of this study was to explore the potential mechanisms underlying performance changes linked to different warm-up stretch modalities. Twenty-one male collegiate-semiprofessional soccer players (age, 20.8 ±2.3 years) performed under 3 different warm-up conditions: a no-stretch warm-up (WU), a warm-up including static passive stretches (SPS), and a warm-up incorporating static dynamic stretches (SDS). Countermovement jump, drop jump, peak torque, heart rate, core temperature, movement kinematics, and electromyography (EMG) were recorded for each intervention. Significant increases (p < 0.001) in performance were recorded for the countermovement, drop jump, and peak torque measures when the SDS was compared with the WU and SPS trials. When mechanism data were analysed, heart rate was significantly higher (p < 0.001) in the SDS condition compared with the SPS and WU conditions (a pattern also shown with core temperature), whereas the WU condition heart rate was also significantly higher than the SPS condition heart rate. When EMG data were examined for the rectus femoris muscle, significantly greater (p < 0.01) muscle activity was observed in the SDS condition compared with the SPS condition. It seems the most likely mechanisms to explain the increase in performance in the SDS condition compared with the SPS condition are increased heart rate, greater muscle activity, and increased peak torque.